Effectiveness of Season Long Training Programme on Knowledge Levels in Kurnool District of Andhra Pradesh (Indian Journal of Extension Education, 2021)
The study was undertaken to know the effectiveness of season long training programme imparted to Village Agriculture Assistants (VAAs) in Kurnool district of Andhra Pradesh by DoA (Department of Agriculture) during kharif 2020. One-group pre and post evaluation design was employed for conducting a formative evaluation. The knowledge tests were administered to 113 VAAs, before and after the training programme. The results showed that there was a significant knowledge gain in subjects like crop production, plant protection and general agriculture in terms of qualification wise, division wise and subject wise. The pre-training mean knowledge score of the trainees was 37.95, which increased to 53.77 after the training. There was an increase of 15.82 in the mean knowledge score, which is significant at the level p < 0.01. In the correlation analysis education, experience, social participation, rural back ground and land holding were found to have significant relationship with knowledge levels of the VAAs. Majority of the respondents expressed in their feedback that they were ‘satisfied ‘regarding its usefulness in enhancing knowledge, appropriateness of the content & its relevancy, stimulation of inquisitiveness, arousal of curiosity & interest.